Improving Activity and Learning Outcomes by Using Think Pair Share (TPS) Type with Card - Fajar Ari Rosidi (Universitas Islam Jember, 2017)
The purpose of the research to describe the using of Think Phair Share (TPS) with card for increasing the students activities and to describe the using of Think Phair Share (TPS) with card for increasing the students learning outcomes. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VII at MTs Raudlatul Ulum Panti. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: TPS, card, students’ activity, learning outcomes